FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN IBU BALITA KE POSYANDU - Elyana Mafticha; Muhammad Himawan Saputra; Tri Widiarti, Maya Tri Widiarti; Hesti Yusiani (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2025)
Integrated Service Post (Posyandu) is a basic health activity organized from, by and for the community assisted by health workers in a work area of the Health Center. The existence of posyandu in the community plays an important role, but there are still many community members who have not made full use of it. Type of quantitative research uses an observational analytical method with a cross sectional approach. The population of all mothers under five (aged 12-59 months) is 125. Accidental Sampling technique as many as 95 respondents. The independent variables were knowledge, perception of affordability and family support, while the dependent variable was the visit of mothers under five. The data was processed through editing, coding, scoring, and data tabulation, analyzed using the Spearman Rank test. The research results showed that the majority (63%) of mothers under five actively visited the Posyandu in Deket Agung Village, the majority (64%) of mothers under five had sufficient knowledge, the majority (60%) had family support in the sufficient category, and the majority (57%) perceived reachability of the posyandu. The results of the Spearman Rank correlation test with a significance value of p value (0.001) α (0.05) with a correlation value (r) of Spearman Rank of knowledge of 0.833, perception of affordability of 0.568 and family support of 0.545. So that H1 is accepted, there is a relationship between knowledge, perception of affordability, family support and visits by mothers under five years old. The conclusion of the study is that knowledge, perception of affordability, and family support are factors influencing the visit of mothers under five to the posyandu. It is suggested that the posyandu can hold various activities to increase the motivation of mothers to visit the posyandu as well as provide varied and interesting additional food, as well as provide guidance to husbands/families so that they can play an active role.